Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 3 - Equations and Problem Solving - Chapter 3 Review Problem Set - Page 137: 18



Work Step by Step

Using the properties of equality, the value of the variable that satisfies the given equation, $ -(t-3)-(2t+1)=3(t+5)-2(t+1) ,$ is \begin{array}{l}\require{cancel} -t+3-2t-1=3t+15-2t-2 \\\\ -t-2t-3t+2t=15-2-3+1 \\\\ -4t=11 \\\\ t=\dfrac{11}{-4} \\\\ t=-\dfrac{11}{4} .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.